Sodium hydroxide/silane treated kenaf fibre in unsaturated polyester matrix: effects of fibres length and fibres loading towards the composites flexural and morphological properties / Muhammad Mustakim Mohd Ghaztar, Nik Noor Idayu Nik Ibrahim and Ahmad Zafir Romli - Mohd Ghaztar, Muhammad Mustakim; Nik Ibrahim, Nik Noor Idayu; Romli, Ahmad Zafir (Universiti Teknologi MARA, 2022)
The fibre behaviour is a critical aspect that will determine the deformation of the composite since it highly relies on its physical and chemical properties. This paper focus on the effect of similar fibres aspect ratio (L/D) with different length of untreated Kenaf fibre and Sodium Hydroxide/silane treated Kenaf fibres on the flexural properties of the composites. The treated and untreated kenaf fibre at two different fibre lengths (A: 0.4 cm and B: 2.9 cm) were fabricated at low filler loadings (5,10,15%) and high filler loadings (45,50,55%). The results showed an improvement in the flexural stress (7-44 %) and modulus (6-46 %) with the application of treatments for both A- and B- fibre categories. The optimum result was achieved from the treated samples at a shorter A-fibre composite, although the aspect ratio between A and B-fibre samples are similar. The chemical treatment coalition might improve the surface interaction and, at shorter fibre length, it affects the fibres compact-ability that led to an improvement in stress distribution and low voids formation as supported by the observation on the composite's fractured surface where traces of matrix observed on the surface of pull-out fibres. From the fractographic analysis, the fibres morphological condition before the fabrication is one of the important factors to consider since it can affect the end-properties of the composites.